2023
DOI: 10.1002/mp.16712
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: Exploring the detectability of coronary calcification using ultra‐high‐resolution photon‐counting‐detector CT

Shaojie Chang,
Liqiang Ren,
Shanshan Tang
et al.

Abstract: BackgroundCoronary calcification is a strong indicator of coronary artery disease, and patients with a “zero” coronary calcification score have a much lower risk of future cardiac events than those with even small amounts of calcium. However, false‐negative (incorrect zero scores) may occur if small calcifications are missed at CT due to limited spatial resolution.PurposeTo demonstrate lower limits of detection for coronary calcification using an ultra‐high‐resolution (UHR) mode on a clinical photon‐counting‐d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…PCDs have shown promise in improving the accuracy of CAC score quantification, which, in conventional CT scanners, is affected by partial volume effects that impair the identification of thin calcifications, leading to an underestimation of the CAC burden, and blooming artifacts that cause an overestimation of the CAC burden. First, phantom studies demonstrated the PCCT's enhanced capabilities in the detection and characterization of small or subtle calcifications, compared to conventional CT systems [98,99]. Of note, it has been shown that monoenergetic reconstructions on PCCT can accurately evaluate the CAC and that there is a decline in the CAC score when QIR strength increases and monoenergetic levels rise [100].…”
Section: Coronary Artery Assessmentmentioning
confidence: 99%
“…PCDs have shown promise in improving the accuracy of CAC score quantification, which, in conventional CT scanners, is affected by partial volume effects that impair the identification of thin calcifications, leading to an underestimation of the CAC burden, and blooming artifacts that cause an overestimation of the CAC burden. First, phantom studies demonstrated the PCCT's enhanced capabilities in the detection and characterization of small or subtle calcifications, compared to conventional CT systems [98,99]. Of note, it has been shown that monoenergetic reconstructions on PCCT can accurately evaluate the CAC and that there is a decline in the CAC score when QIR strength increases and monoenergetic levels rise [100].…”
Section: Coronary Artery Assessmentmentioning
confidence: 99%